Literature Review: Financial Management in Hospitals Using Process Improvement Methods - Putra, Agung Manik Septiana; Nasution, Musthofa Lutfi; Pratiwi, Widya; Atmanto, Kusumo Adi Arji; Paramarta, Vip (Jurnal Indonesia Sosial Sains, 2024)
Financial management in hospitals faces significant challenges due to increasing healthcare costs and the demand to maintain high-quality patient care. Process Improvement methods such as Lean and Continuous Improvement have been adopted by hospitals to address these challenges. This study aims to review the literature regarding the impact of implementing Lean and Continuous Improvement methodologies on hospital financial management. The research methodology employed a systematic approach, analyzing studies published between 2018 and 2023. The results of the review showed that the implementation of Lean and Continuous Improvement methods significantly improved operational efficiency, leading to cost reductions of up to 30%, while simultaneously enhancing patient care quality and staff satisfaction. In conclusion, these methodologies offer a sustainable approach for hospitals to manage financial pressures without compromising the quality of care. Hospitals are encouraged to adopt these strategies to achieve long-term financial stability and operational excellence.